Major Schemes of the Ministry of MSME to Generate Employment Opportunities and Marketing - Dr. H M Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The M/o MSME organizes various schemes which are aimed at different purpose. The sample schemes which are presented in this article are: (a) Schemes for credit and financial assistance like PMEGP and Credit Trust Fund for MSEs ; (b) Schemes for Skill Development and Training like Promotion of Innovation, Rural Industries and Entrepreneurship ; (c) Schemes for Infrastructure Development, such as, Fund for Regeneration of Traditional Industries as well as Cluster Development Programme (CDP) ; (d) Schemes for Marketing Assistance like providing financial assistance to Khadi institutions under MPDA ; (e) Schemes for Technology Upgradation and Competitiveness like MSME Champions Scheme involving three Components like MSME Sustainable (ZED) ; MSME Competitive (Lean) and MSME (Innovative) ; (f) Other Schemes like UNIDO, GEF-5 Project and RAMP scheme which are spread across the country. These schemes for MSMEs are revised and updated in the month of February, 2024. Brief descriptions of these schemes are presented in this article.
Keywords: Schemes for MSMEs; PMEGP; MUDRA Yojana; CGTMSE; MSE-CDP; ESDP; ATI; Coir Vikas Yojana; PMS; IC Scheme; SC-ST Hub; ASPORE; Khadi Gramodyog Vikas; MSME in NER & Sikkim; PM Vishwakarma; Tool Rooms and Technical Institutions; SME Champion Schemes; SRI Fund; RAMP Scheme